Manifestations of Formalist Concepts in al-Sakkaki: A Reading in Rhetorical Criticism - Al-Qahtani, Suad Abdullah Al-Mutared (Arts for Linguistic & Literary Studies, 2025)
This paper examines al-Sakkaki’s rhetorical legacy through the lens of Formalist theory, with the aim of identifying the mechanisms of his critical thought, mapping the epistemological system underpinning his work, and tracing the transformations of Arabic rhetoric across pre- and post-Sakkaki contexts. Using Miftaḥ al-Ulum as the primary text, the study adopts a meta-critical approach to analyze the convergence between al-Sakkaki’s rhetoric and Russian Formalist concepts. The findings reveal multiple formalist tendencies: metaphor is treated as a product of formalist cognition where meaning resides in form, whether on the paradigmatic or syntagmatic level; eloquent discourse is classified in graded hierarchies; and informative statements are analyzed across levels of rhetorical effect. Al-Sakkaki’s dedicated discussion of the essence of poetry further aligns with poetics in its attempt to define what constitutes poetic discourse and distinguishes it from prose. Collectively, these features underscore the presence of both explicit and implicit formalist orientations in his work, suggesting that al-Sakkaki anticipated aspects of a formalist and even post-formalist rhetoric with pragmatic extensions.